Standar Epistemologi dan Etika Jurnalisme Digital: Studi Komparasi Indonesia, Australia, dan Britania Raya - Jehalut, Ferdinandus; Wutun, Monika; Swan, Maria Via Dolorosa Pabha (JURNAL KOMUNIKATIO, 2026)
This study compares the ethical and epistemological standards of digital journalism as articulated in legal frameworks, professional codes, and public policies in Indonesia, Australia, and the United Kingdom. Using a descriptive qualitative approach within a constructivist paradigm, it conducts a comparative analysis of relevant legislation, online media guidelines, and journalist safety policies in the three countries. The findings identify three distinct models. Indonesia advances an editorial-ethics model emphasizing verification, correction, the right of reply, and the separation of news and advertising, yet largely neglecting algorithmic power. Australia develops a democracy-news economy model that defines news as essential to democratic participation and regulates bargaining relations between news organizations and platform companies. The United Kingdom establishes a regulatory-protection model that grants special status and procedural safeguards to journalistic content, while strengthening protections for journalists within an online safety regime. The study concludes that renewing the ethical and epistemological foundations of digital journalism requires closer alignment among professional ethics, public policy, and platform regulation to sustain journalism’s credibility as an epistemic authority. It calls for intensified collaboration among policymakers, media organizations, regulators, and journalism educators to address datafication, algorithmic opacity, and journalist safety in future regulatory reforms.